Hubungan Aktivitas Fisik Dengan Fungsi Kognitif Pada Lansia Di Posyandu Lansia Kelurahan Rambutan Kecamatan Ciracas Kota Jakarta Timur dan Tinjauannya Menurut Pandangan Islam: The Relationship Between Physical Activity and Cognitive Function in The Elderly at The Elderly Posyandu, Rambutan Village, Ciracas District, East Jakarta City and its Review According to Islamic Views - Regina Amanda Putri; Luthfiana, Anna; Prasetyo, Edi (Junior Medical Journal, 2024)
KATA KUNCI Lansia, Aktivitas Fisik, Fungsi Kognitif, Kesehatan, Fisik ABSTRAK Penelitian ini bertujuan untuk mengevaluasi hubungan antara aktivitas fisik dan fungsi kognitif pada lansia di Posyandu Lansia Kelurahan Rambutan, Kecamatan Ciracas, Kota Jakarta Timur. Melalui pendekatan kuantitatif dengan desain studi deskriptif analitik dan penelitian cross-sectional, data dikumpulkan dari 84 responden lansia menggunakan kuesioner Mini-Mental State Examination (MMSE) untuk mengukur fungsi kognitif dan Indeks Barthel untuk mengukur aktivitas fisik. Hasil analisis data menunjukkan adanya hubungan yang signifikan antara aktivitas fisik dan fungsi kognitif pada lansia (p-value = 0,033). Mayoritas responden menunjukkan tingkat kemandirian dalam aktivitas fisik, namun terdapat variasi tingkat kemandirian tersebut. Gangguan kognitif, terutama pada aspek memori dan bahasa, terlihat pada responden dengan fungsi kognitif normal. Temuan ini mengakui pentingnya perawatan dan penghormatan terhadap lansia serta mendukung aktivitas fisik sebagai upaya menjaga kesehatan. Menjaga aktivitas fisik secara teratur dapat memainkan peran kunci dalam memelihara dan meningkatkan fungsi kognitif lansia yang menekankan pentingnya menjaga kesehatan. Menjaga aktivitas fisik secara teratur dapat memainkan peran kunci dalam memelihara dan meningkatkan fungsi kognitif lansia, sesuai dengan nilai-nilai Islam yang menekankan pentingnya menjaga kesehatan. KEYWORDS Elderly, Physical Activity, Cognitive Function, Health, Physical ABSTRACT This study aims to evaluate the relationship between physical activity and cognitive function in elderly people at the Posyandu for the Elderly, Rambutan Village, Ciracas District, East Jakarta City. Through a quantitative approach with a descriptive analytical study design and cross-sectional research, data was collected from 84 elderly respondents using the Mini-Mental State Examination (MMSE) questionnaire to measure cognitive function and the Barthel Index to measure physical activity. The results of data analysis show that there is a significant relationship between physical activity and cognitive function in the elderly (p-value = 0,033). The majority of respondents indicated a level of independence in physical activity, but there were variations in the level of independence. Cognitive impairment, especially in aspects of memory and language, was seen in respondents with normal cognitive function. This finding is recognizes the importance of caring for and respecting the elderly and supports physical activity as an effort to maintain health. Maintaining regular physical activity can play a key role in maintaining and improving the cognitive function of the elderly, in accordance values ​​which emphasize the importance of maintaining health. Maintaining regular physical activity can play a key role in maintaining and improving the cognitive function of the elderly, in accordance with Islamic values ​​which emphasize the importance of maintaining health.